Pelatihan penulisan karyah ilmiah Penelitian Tindakan Kelas bagi guru-guru SMK - Muhammad Yahya; Rissa Megavitry (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The partner of this Community Partnership Program (PKM) is the teachers at Vocational High School 9 Makassar. The problems were the teachers at Vocational High School 9 Makassar still constrained in carrying out classroom action research which included difficulties in understanding the specific learning problems in their class whether in the area of media, methods, class organizing, policies, or evaluations so as to hamper the fulfillment of requirements in improvement rank/section. With the training in making classroom action research the teachers can be more productive in developing various types of classroom action research. The methods used were: lectures, discussions, question and answer, and demonstrations. The results achieved were (1) the partners know about basic concept of classroom action research, (2) the partners can develop methods/ implementation of class action research, (3) the partners can make the proposal of classroom action research, (4) the partners can carry out the classroom action research, and (5) the partners know how to make classroom action research report.